Personality and Friendship Satisfaction in Daily Life: Do Everyday Social Interactions Account for Individual Differences in Friendship Satisfaction?. Issue 2 (March 2015) - Wilson, Robert E.; Harris, Kelci; Vazire, Simine
Abstract: Who are the people who maintain satisfying friendships? And, what are the behaviours that might explain why those people achieve high friendship satisfaction? We examined the associations between personality (self‐reports and peer‐reports) and friendship satisfaction (self‐reports) among 434 students. We also examined whether role personality (how people act with their friends) and quantity and quality of social interactions using ecological momentary assessment mediate the associations between personality and friendship satisfaction. Extraversion, agreeableness, conscientiousness and (low) neuroticism were associated with higher levels of friendship satisfaction. These associations could not be accounted for by individual differences in role personality. In addition, our results suggest that quantity of time spent with friends and quality of friend interactions (depth of conversation, self‐disclosure and lack of emotion suppression), although associated with friendship satisfaction, do not account for the associations between trait personality and friendship satisfaction. Future research should examine other potential interpersonal processes that explain why some people are more satisfied with their friendships than others and the consequences of friendship satisfaction (e.g. for well‐being). Copyright © 2015 European Association of Personality Psychology